Discovery of Metal-poor and Distant Pre–Main Sequence Candidates in WLM with JWST - Venu M. Kalari; Ricardo Salinas; Morten Andersen; Guido De Marchi; Monica Rubio; Jorick S. Vink; Hans Zinnecker (The Astrophysical Journal Letters)
We present the discovery of 12 metal-poor and ​​​distant pre–main sequence (PMS) candidates in the dwarf irregular galaxy Wolf–Lundmark–Melotte ∼968 kpc away, at a present-day metallicity of [Fe/H] ∼ –0.9. These candidates have masses between 1.25 and 5 M _⊙ , with ages <10 Myr, and exhibit significant near-infrared excesses at 2.5 and 4.3 μ m. They are concentrated within a cluster roughly 10 pc (2″) across, situated in the H ii region [HM95]-9. These are the most distant and metal-poor PMS stars known, and they can offer new quantitative insights into star formation at low metallicities.